2005
DOI: 10.1016/j.jcrs.2004.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posterior capsule opacification rates between hydrophilic and hydrophobic single-piece acrylic intraocular lenses

Abstract: The rate of PCO was significantly higher with the hydrophilic IOL. However, the results cannot be attributed to the IOL material alone as they show the importance of both IOL material and design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
82
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 26 publications
3
82
0
7
Order By: Relevance
“…These results, however, cannot be attributed to the difference in IOL materials alone because numerous studies have reported that PCO rates in hydrophilic acrylic IOLs are much higher than those in hydrophobic IOLs. 3,17,18 It might be inferred that heparin has some PCO preventive effects, but the degree of those preventive effects does not exceed those of the hydrophobic acrylic IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results, however, cannot be attributed to the difference in IOL materials alone because numerous studies have reported that PCO rates in hydrophilic acrylic IOLs are much higher than those in hydrophobic IOLs. 3,17,18 It might be inferred that heparin has some PCO preventive effects, but the degree of those preventive effects does not exceed those of the hydrophobic acrylic IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that fewer infl ammatory cells and pigments are deposited on HSM IOLs than on non-HSM IOLs and that the early postoperative anterior chamber reaction of HSM IOLs is less than that of non-HSM IOLs. [3][4][5] It is postulated that the HSM IOL, which has a hydrophilic surface, leads to a reduction Jpn Abstract Purpose: To compare posterior capsular opacifi cation (PCO) in a heparin-surface-modifi ed (HSM) hydrophilic acrylic intraocular lens (IOL) and a hydrophobic acrylic IOL.Methods: Seventy-eight patients with simple cataract were randomized to receive either the BioVue 3 HSM hydrophilic acrylic IOL (Ophthalmic Innovations International, Ontario, CA, USA) (n = 38) or the Sensar AR40e hydrophobic acrylic IOL (AMO, Santa Ana, CA, USA) (n = 40). Another 99 patients with complicated cataract received either the BioVue 3 (n = 49) or the Sensar AR40e IOL (n = 50).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 In our study, the IOLs we compared are similar except for the surface. They both have a 1-piece design, square-edged optics, and no haptic angulation.…”
Section: Discussionmentioning
confidence: 98%
“…The use of hydrophilic lenses in the adult population has been reported by many studies, with mixed outcomes. 17,18 However, there are very few studies on the use of hydrophilic lenses in a pediatric population. Most of these studies have shown good surgical and visual outcomes in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%